Representations of Girlhood and Girl Stereotypes in Victoria Aveyards’ The Red Queen Collection - Masoumeh Soltani; Laleh Atashi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2021)
Given the fact that girlhood studies is a new area of investigation which intriguingly demonstrates various ways through which girlhood is structured by different social and cultural codes, we intend to examine girl characters in The Red Queen collection as it was the New York Times Best Selling series. This investigation reveals the way cultural and social norms prescribe specific gender roles and shape different versions of girl characters in this series. To find girl stereotypes in The Red Queen collection, such girlhood theories as Girl Power, Reviving Ophelia, #LIKEAGIRL, Girl Effect and Girl Up have been taken into consideration. Various depictions of girlhood in The Red Queen collection are represented through characters who have different ethnic backgrounds and come from different social classes. This implies that the formation of girl identity has a lot to do with social, economic, political and cultural structures. However, identity formation, as we see in the collection, is an ongoing process and can change in the course of an individual’s self-development.